2021
DOI: 10.1111/nmo.14224
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and long‐term outcomes in pediatric cyclic vomiting syndrome: A 9‐year experience at three tertiary academic centers

Abstract: Background: Pediatric cyclic vomiting syndrome (CVS) is a little-known clinical condition, frequently diagnosed with delay. This study aims to describe the clinical presentation and management and to define possible predictive factors of the disease outcome. Methods:In this retrospective study, all children who were diagnosed with CVS during the period 2010-2019 in three tertiary academic centers were included. The association between clinical variables and outcomes was investigated.Key Results: Fifty-seven ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 27 publications
2
7
0
2
Order By: Relevance
“…There were no other baseline predictors including episode characteristics and comorbidities of progression to ANS dysfunction. This corroborates recent findings from a large, tertiary center study of children with CVS where no predictors of disease outcome were found, but rather a high inter-individual variability in outcomes (23).…”
Section: Discussionsupporting
confidence: 91%
“…There were no other baseline predictors including episode characteristics and comorbidities of progression to ANS dysfunction. This corroborates recent findings from a large, tertiary center study of children with CVS where no predictors of disease outcome were found, but rather a high inter-individual variability in outcomes (23).…”
Section: Discussionsupporting
confidence: 91%
“…More than half (56%) had resolution of vomiting but 26% developed migraine headache and 7% recurrent abdominal pain. 15 This is consistent with other retrospective pediatric studies; one study in Ireland of 41 children showed that 61% had resolution of vomiting but 42% continued to have headaches and 37% had abdominal pain. There were no specific predictors of response that were noted including use of prophylactic medications.…”
Section: Predictors Of Persistent Cvs Episodessupporting
confidence: 91%
“…Studies in children have shown that 56-61% have spontaneous resolution of CVS episodes though a subset develop migraine headache over time. 15,16 Whether adult-onset or a non-resolving pediatric disorder, the natural history and clinical outcomes in adult CVS sufferers are unknown. The aim of this study was to clinically characterize a large cohort of adult patients with CVS followed at a tertiary referral center over a span of 12 years and determine the natural history data and clinical outcomes in these patients.…”
mentioning
confidence: 99%
“…Dans une récente étude italienne auprès de 57 enfants, les chercheurs n'ont trouvé aucune différence dans l'âge de l'apparition, le sexe, la durée du suivi, la sévérité, la médication, les antécédents familiaux ou les facteurs déclencheurs entre les enfants chez qui les vomissements avaient cessé et ceux chez qui ils avaient perduré, ou entre ceux qui souffraient de migraine et ceux qui n'en avaient pas lors du suivi 7 . À leur congé de l'hôpital, 47 enfants (82 %) ont commencé un traitement prophylactique à long terme à la flunarizine, à la cyproheptadine, au topiramate ou aux inhibiteurs de la pompe à protons.…”
Section: Traitement Prophylactiqueunclassified
“…Le syndrome des vomissements cycliques cause une morbidité considérable, et la moitié des enfants ont besoin d'une réhydratation par intraveineuse 6 . Dans une récente étude rétrospective réalisée dans 3 centres universitaires tertiaires auprès de 57 enfants, des antécédents familiaux de migraines ont été signalés chez la moitié des enfants (47 %), et la plupart d'entre eux avaient au moins un épisode chaque mois (63 %) et au moins 1 prodrome connu (75 %) 7 . L'âge moyen (ET) à l'apparition des symptômes chez les enfants dans une étude se situait à 5,7 (0,3) ans et l'âge moyen au diagnostic était de 8,0 (0,3) ans 2 .…”
unclassified